LIVING ISLAM Apa dan Mau ke Mana? - H. Zuhri (UIN Sunan Kalijaga Yogyakarta, 2018)
Discussing the Islam in the context of everyday life, in various aspects, perspectives, and wide variety of geo- graphical field, can be replicated with the term of Living Islam. Islam in the society is now understood by a set of methodologies and scientific paradigms and has been carried out by intellectuals from both internal Islam such as Akbar S. Ahmed and from external Islam as Islamic anthropology or anthropology about Islam. Whatever the name suggests, anthropology still impressed only the human dimension, Living Islam offers a comprehensive perspective and integrated with various other scientific disciplines. This paper seeks to define living Islam in society theoretically with a framework of thought and practical research methods that can be used as a guide for research on Living Islam.